External effects in the 400-m hurdles race - Quinn, M. D. (Journal of Applied Biomechanics, 2010)
A mathematical model based on a differential equation of motion is used to simulate the 400-m hurdles race for men and women. The model takes into account the hurdler`s stride pattern, the hurdle clearance, and aerobic and anaerobic components of the propulsive force of the athlete, as well as the effects of wind resistance, altitude of the venue, and curvature of the track. The model is used to predict the effect on race times of different wind conditions and altitudes. The effect on race performance of the lane allocation and the efficiency of the hurdle clearance is also predicted. The most favorable wind conditions are shown to be a wind speed no greater than 2 m/s assisting the athlete in the back straight and around the second bend. The outside lane (lane 8) is shown to be considerably faster than the favored center lanes. In windless conditions, the advantage can be as much as 0.15 s for men and 0.12 s for women. It is shown that these values are greatly affected by the wind conditions.